2017
DOI: 10.1128/mbio.00031-17
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Junctional Adhesion Molecule 1 as a Functional Receptor for the Hom-1 Calicivirus on Human Cells

Abstract: The Hom-1 vesivirus was reported in 1998 following the inadvertent transmission of the animal calicivirus San Miguel sea lion virus to a human host in a laboratory. We characterized the Hom-1 strain and investigated the mechanism by which human cells could be infected. An expression library of 3,559 human plasma membrane proteins was screened for reactivity with Hom-1 virus-like particles, and a single interacting protein, human junctional adhesion molecule 1 (hJAM1), was identified. Transient expression of hJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
(89 reference statements)
0
20
0
Order By: Relevance
“…1 ). Feline calicivirus (FCV) and Hom-1 calicivirus employ junctional adhesion molecule A (JAM-A) and related proteins as receptors ( 36 , 37 ). The cryo-EM structure of the FCV capsid in complex with the two Ig-like extracellular domains of fJAM-A indicates this receptor also binds to the P2 subdomain, although the receptors appear to engage the top of the P domain near the dimer interface ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Feline calicivirus (FCV) and Hom-1 calicivirus employ junctional adhesion molecule A (JAM-A) and related proteins as receptors ( 36 , 37 ). The cryo-EM structure of the FCV capsid in complex with the two Ig-like extracellular domains of fJAM-A indicates this receptor also binds to the P2 subdomain, although the receptors appear to engage the top of the P domain near the dimer interface ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other powerful methods to be used in combination with glycomics and proteomics include RNA interference, CRISPR/Cas9 knockout, genome-wide haploid screens, cell-based arrays, drug-based approaches, and utilization of the microarray-characterized set of cells provided by US National Cancer Institute. We refer the reader elsewhere for further information on these methods [160][161][162][163][164][165][166]. A clear advantage of labelfree glycomics and proteomics technologies is, however, the minimal system perturbation in particular when untagged endogenous bait glycans and proteins are used.…”
Section: Alternative Approaches For Receptor Discoverymentioning
confidence: 99%
“…Recently, it was observed that some HuNoVs and monkey recoviruses also utilize SAs as attachment factors ( 29 , 30 ). Finally, proteinaceous cellular surface structures were identified as receptors for a few caliciviruses, such as CD300lf and CD300ld for MNV ( 31 , 32 ) and junctional adhesion molecule-1 (JAM-1) for FCV and Hom-1 calicivirus ( 33 – 35 ).…”
Section: Introductionmentioning
confidence: 99%